Elastin genetic point mutation and the risk of pelvic organ prolapse - N. Haya; I. Feferkorn; F. Fares; N. Azzam; R. Auslender; Y. Abramov (IMR Press, 2020)
Aim: A missense mutation in the elastin gene (g28197A > G) is associated with an increased risk for inguinal hernias. Due to the shared epidemiological and pathophysiological features between pelvic organ prolapse (POP) and inguinal hernias, the authors hypothesized that a similar association exists between elastin gene polymorphism and POP. Materials and Methods: Patients of Ashkenazi Jewish origin with advanced (stage III-IV) POP (as assessed by POP-Q) and healthy controls were compared for the presence of the elastin gene g28197A > G missense mutation. Results: The missense mutation in the elastin gene was not found in neither the study or the control group. Conclusion: The elastin gene g28197A > G missense mutation was not found to be associated with an increased risk for POP.